1985
DOI: 10.1136/ard.44.9.621
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens and toxic reactions to sodium aurothiopropanol sulphonate and D-penicillamine in patients with rheumatoid arthritis.

Abstract: SUMMARY One hundred and forty-one patients with rheumatoid arthritis treated with aurothiopropanol sulphonate or D-penicillamine, or both were examined for HLA antigens to investigate the genetic influence on the occurrence of different adverse reactions during therapy. All 13 patients possessing HLA-DR3 had toxic reactions. The relative risk for DR3 positives of developing skin eruptions or proteinuria was calculated to be 10*5 times and seven times respectively that of DR3 negatives. The incidence of DR7 ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Several studies have shown that HLA polymorphism contributes to susceptibility to adverse drug reactions 4,5,20. To the best of our knowledge, the present report is the first to show an association of DRB1*08:02 with BI-Pro in Japanese RA patients.…”
Section: Discussionsupporting
confidence: 59%
“…Several studies have shown that HLA polymorphism contributes to susceptibility to adverse drug reactions 4,5,20. To the best of our knowledge, the present report is the first to show an association of DRB1*08:02 with BI-Pro in Japanese RA patients.…”
Section: Discussionsupporting
confidence: 59%
“…DNA typing of HLA-DR alleles from patients with RA confirmed the shared epitope hypothesis, because HLA-DRB1*0401, 0404, 0405, 0408, HLA-DRB1*0101 and DRB1*1402 share the same sequence at positions 70–74 in the third exon, but DRB1*0402 and others do not [7, 14]. HLA antigens have also been reported to be associated with the reactive side effects of drugs to RA [15, 16, 17, 18, 19, 20, 21]and also with the severity of the disease [22, 23, 24, 25, 26, 27, 28, 29, 30]as well as with the susceptibility to RA with extra-articular manifestations [25, 31, 32, 33, 34, 35]. …”
Section: Introductionmentioning
confidence: 62%
“…These nephropathies, especially toxic nephropathy and secondary amyloidosis, could determine the prognosis of patients [36, 40]. HLA-DR3 has been reported to be associated with proteinuria after treatment with D -penicillamine and sodium aurothiomalate in Caucasian patients [16, 17]. Panayi et al [15]described that serological HLA-DR3 and/or serological HLA-DR15 were associated with a toxic reaction against kidney under gold therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calin (1980) suggested that genetic predisposition plays a role. Adverse effects, especially renal, with D-penicillamine have been found to be more frequent in patients with rheumatoid arthritis who belong to the HLA-Bs (Dequeker et al 1984) or DR3 (Perrier et al 1985) groups. Other studies, however, have shown that adverse effects with D-penicillamine are completely unpredictable, even if the patient has previously suffered toxicity with gold salts (Kean et al 1982).…”
Section: Pharmacokinetic Drug Interactionsmentioning
confidence: 97%